Voltage-driven beam bistability in a reorientational uniaxial dielectric - Armando Piccardi (APL Photonics, 2016)
We report on voltage controlled bistability of optical beams propagating in a nonlocal reorientational uniaxial dielectric, namely, nematic liquid crystals. In the nonlinear regime where spatial solitons can be generated, two stable states are accessible to a beam of given power in a finite interval of applied voltages, one state corresponding to linear diffraction and the other to self-confinement. We observe such a first-order transition and the associated hysteresis in a configuration when both the beam and the voltage reorientate the molecules beyond a threshold.